2017
DOI: 10.1186/s12978-017-0289-2
|View full text |Cite
|
Sign up to set email alerts
|

Moving from legality to reality: how medical abortion methods were introduced with implementation science in Zambia

Abstract: BackgroundAlthough abortion is technically legal in Zambia, the reality is far more complicated. This study describes the process and results of galvanizing access to medical abortion where abortion has been legal for many years, but provision severely limited. It highlights the challenges and successes of scaling up abortion care using implementation science to document 2 years of implementation.MethodsAn intervention between the Ministry of Health, University Teaching Hospital and the international organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Medical abortion (which in Zambia may be either using mifepristone and misoprostol in combination or misoprostol alone) was introduced to Zambia in 2009 14 and is already the more frequently used method of both TOP and PAC. This is an important development since medical abortion is a safe and effective method of service delivery that can be provided discreetly and conveniently to women, with fewer physical barriers than surgical services (such as manual vacuum aspiration or dilation and evacuation, depending on gestation), and has the potential to reduce maternal mortality from unwanted pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical abortion (which in Zambia may be either using mifepristone and misoprostol in combination or misoprostol alone) was introduced to Zambia in 2009 14 and is already the more frequently used method of both TOP and PAC. This is an important development since medical abortion is a safe and effective method of service delivery that can be provided discreetly and conveniently to women, with fewer physical barriers than surgical services (such as manual vacuum aspiration or dilation and evacuation, depending on gestation), and has the potential to reduce maternal mortality from unwanted pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Within health facilities, conscientious objection, lack of training, high staff turnover and stigma all present further barriers to care. 14 15 …”
Section: Introductionmentioning
confidence: 99%
“…8 Several articles describe specific difficulties in guaranteeing equitable access to services in South Africa, Zambia, and India, and the interventions designed to address these problems. [9][10][11] Comprehensive reviews of a single country's program, including health system level implementation steps, successes, and difficulties exist for India, 12 Mexico City, 13 and South Africa, 14 but there are no comparative data to guide future program implementation. A recent five-country case study developed to inform the WHO guideline on task sharing found limited documentation of the implementation processes undertaken.…”
Section: Andmentioning
confidence: 99%
“…One multicountry report did offer a framework for the successful implementation of abortion services; it relied primarily on a review of published and “grey” literature although it included some interviews with key informants . Several articles describe specific difficulties in guaranteeing equitable access to services in South Africa, Zambia, and India, and the interventions designed to address these problems . Comprehensive reviews of a single country's program, including health system level implementation steps, successes, and difficulties exist for India, Mexico City, and South Africa, but there are no comparative data to guide future program implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of medical induced abortion has revolutionized the way abortion services are provided, and has improved access to abortion. In low‐resource settings with few trained surgical providers, medical abortion provides a safe and effective non‐surgical option . Medical abortion drugs are widely available from pharmacies and drug sellers; even in restrictive settings, medication such as misoprostol can be purchased over the counter for other indications and used to induce an abortion .…”
Section: Introductionmentioning
confidence: 99%